Corporeal Abjection and Hopefulness in Oscar Wilde's "Charmides" (1881). - Hueso-Vasallo, Manuel (Universidad de Murcia, 2025)
This paper addresses the potential relationship between corporality, abjection, and hope in Oscar Wilde’s “Charmides” (1881). The main aim of inspecting this connection is to establish how Wilde makes use of abjection in order to defend the idea that sexual dissidence can, indeed, offer the possibility of hope. In other words, the paper focuses on how Wilde describes abject bodies and abject bodily acts in the poem in a way that ultimately defies the social and moral conventions of his period. It argues that acts that may be considered abject –such as same-sex desire– can be hopeful when addressed from a different perspective. This paper hopes to establish a clear connection between the poem, the abject, and Wilde’s defiance of the sexual mores of his period.
Keywords: Teoría queer; Poesía inglesa - S. XIX; Wilde, Oscar - Crítica e interpretación; Oscar Wilde; abjection; Queer Studies; Victorian poetry; Hope